2008
DOI: 10.1002/ijc.23392
|View full text |Cite
|
Sign up to set email alerts
|

CCL17 and CCL22 chemokines within tumor microenvironment are related to accumulation of Foxp3+ regulatory T cells in gastric cancer

Abstract: It has been reported that an increased population of regulatory T cells (Tregs) is one of the reasons for impaired anti-tumor immunity. Recently, Foxp3 has been reported as a reliable marker of Tregs. The authors investigated the frequency of Foxp3 1 Tregs within CD4 1 cells in TILs, regional lymph nodes and PBLs of gastric cancer patients (n 5 45). Furthermore, to elucidate the mechanisms behind Treg accumulation within tumors, they evaluated the relationship between CCL17 or CCL22 expression and the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
228
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(256 citation statements)
references
References 35 publications
14
228
4
1
Order By: Relevance
“…In this study, several lymphoma cell lines expressed CCL17 and/or CCL22. It has also been reported that high levels of CCL17 and CCL22 were detected in various tumours, such as lung cancer, 43 gastric cancer, 44 B-cell non-Hodgkin lymphoma, 45 Hodgkin's lymphoma 46 and peripheral T-cell lymphomas. 47 Among the lymphomas, CCL17 is specifically expressed in classical Hodgkin's lymphoma, 46,48 while CCL22 is expressed in nodular lymphocyte-predominant Hodgkin9s lymphoma and B-cell non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, several lymphoma cell lines expressed CCL17 and/or CCL22. It has also been reported that high levels of CCL17 and CCL22 were detected in various tumours, such as lung cancer, 43 gastric cancer, 44 B-cell non-Hodgkin lymphoma, 45 Hodgkin's lymphoma 46 and peripheral T-cell lymphomas. 47 Among the lymphomas, CCL17 is specifically expressed in classical Hodgkin's lymphoma, 46,48 while CCL22 is expressed in nodular lymphocyte-predominant Hodgkin9s lymphoma and B-cell non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 94%
“…7,8 Elevated levels of CCL22 have been described in many human tumors, including B-CLL, Hodgkin lymphoma, breast, lung and gastrointestinal cancers. [9][10][11][12][13][14] For many of these tumors, elevated intratumoral CCL22 concentrations are associated with a higher tumor infiltration by Treg. Treg are an inhibitory subset of T helper cells, whose function is to suppress cytotoxic T effector cell functions, [15][16][17] involving cell-contact dependent and cell-contact independent mechanisms such as consumption of IL-2, expression of the cellsurface antigen CTLA-4 and secretion of inhibitory cytokines such as TGF-b and IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, decrease in CXCL10 secretion from DCs via adenosine may increase tumor growth. On the other hand, CCL17 has been linked to accumulation of FOXP3 + regulatory T cells (T regs ) in gastric cancer [129]. In a recent study, selective knock down of CCL22 and CCL17 expression by siRNA decreased the ratios of CD4 + to CD8 + as well as the frequency of T regs recruited by monocyte-derived DCs (MoDCs) [130].…”
Section: Adenosine and Dendritic Cells Interaction In Tumor Environmentmentioning
confidence: 99%